Do Households Anchor their Inflation Expectations? Theory and Evidence from a Household Survey - Joshy Easaw; Roberto Golinelli; Marco Malgarini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
The purpose of the present paper is to study how households form inflation expectations. Using a novel survey-base dataset of Italian households' opinions of inflation we investigate two separate, but related, types of behavior: 'inattentiveness' and 'anchoring'. The present analysis extends the existing literature by incorporating explicitly inflation targets and distinguishing between aggregate and disaggregate dynamics based on demographic groups. In addition, we extend the literature by considering both the short- and long-run dynamics as households update their inflation expectations while also accounting for their state-varying behavior. All these issues provide important insights into understanding actual inflation dynamics and the conduct of monetary policy.
Keywords: D1; D84; E1; E31; C33; 330